Impacts of impurity flux on erosion and deposition of carbon/tungsten rough surfaces. (March 2021) - Dai, S.Y.; Yang, K.R.; Liu, D.H.; Shi, Q.; Cui, B.; Liu, S.G.; Wang, D.Z.
Highlights: SURO simulates deposition of carbon impurity on rough wall surfaces. For low impurity flux, carbon and tungsten substrates maintain to be eroded. For high impurity flux, tungsten and carbon substrates are protected from erosion. Abstract: The influences of impurity flux on erosion and deposition of carbon/tungsten rough surfaces have been investigated with the rough surface code SURO. The temporal evolution of the eroded substrate and deposited impurity areal densities has been studied with different carbon fluxes. For the low impurity flux, the carbon and tungsten substrates maintain to be eroded during the exposure. The tungsten eroded areal density is about 10 10 μm −2, which is two orders of magnitude lower than the carbon substrate. In contrast, for the high impurity flux, both the tungsten and carbon substrates can be protected by the strongly deposited impurity from erosion. The increased impurity flux leads to the transition from erosion to deposition dominated regime for both rough tungsten and carbon surfaces.